Influência das características morfológicas da mandíbula na eficácia da infiltração vestibular com articaína 4% com epinefrina 1:100:000 : Influence of the morphological characteristics of the mandible on the anesthetic efficacy of vestibular infiltration with 4% articaine with 1:100.000 epinephrine - Angelieri, Bruna Milaré, 1988- (2022)
Orientador: José Flávio Affonso de Almeida